Constraints on the CKM angle γ from B± → Dh± decays using D → h±h′∓π0 final states - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2022)
A data sample collected with the LHCb detector corresponding to an integrated luminosity of 9 fb−1 is used to measure eleven CP violation observables in B± → Dh± decays, where h is either a kaon or a pion. The neutral D meson decay is reconstructed in the three-body final states: K±π∓π0; π+π−π0; K+K−π0 and the suppressed π±K∓π0 combination. The mode where a large CP asymmetry is expected, B± → [π±K∓π0]DK±, is observed with a significance greater than seven standard deviations. The ratio of the partial width of this mode relative to that of the favoured mode, B± → [K±π∓π0]DK±, is RADS(K) = (1.27 ± 0.16 ± 0.02) × 10−2. Evidence for a large CP asymmetry is also seen: AADS(K) = −0.38 ± 0.12 ± 0.02. Constraints on the CKM angle γ are calculated from the eleven reported observables.
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, R. Caspary, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und sehr viele weitere Personen]
Gesehen am 17.02.2023